Error Analysis of Sentence-Writing in 3RD Grade Elementary School at SDN Gedanganak 3 - Amanda Kamilla Zulfaa’; Ratih Laily Nurjanah (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to analyse the types of errors commonly found in the English writing of third-grade students at SDN Gedanganak 3. The analysis focuses on four key aspects of writing mechanics: spelling, punctuation, capitalization, and grammar. The data were obtained from a written test involving sentence-writing tasks, and each error was categorized and calculated based on its frequency. The results revealed that the most frequent errors occurred in the punctuation aspect (48.95%), followed by grammar (46.84%), capitalization (41.05%), and spelling (33.68%). These findings indicate that students still face challenges in constructing simple English sentences, particularly in applying writing mechanics accurately. Therefore, English writing instruction should emphasize balanced and focused practice across all mechanical aspects to support students’ overall writing development.